KORELASI ANTARA PENERAPAN PENDEKATAN KONSTRUKTIVISME DENGAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH MATEMATIKA DASAR (Universitas PGRI Sumatera Barat, 2022)
The purpose of this research is to get information about correlation between constructivismapproach with student learning outcomes in basic mathematics lectures. This research uses a descriptive method. Participants in this study are biology education students who take the basic mathematics courses amounting to 28 people. The result of this research shows that there is a significance correlation between the constructivism approach with student learning outcomes in basic mathematics lectures. Keywords: Constructivism Approach, Student Learning Outcomes, Basic Mathematics Lectures